THE INFLUENCE OF ACCOUNTING INFORMATION SYSTEM IMPLEMENTATION AND INTERNAL CONTROL EFFECTIVENESS ON THE PERFORMANCE OF EMPLOYEES (CASE STUDY ON MICRO, SMALL, MEDIUM ENTERPRISES SUBANG REGENCY) - Agnes Sinta Harini; Asep Kurniawan; Indah Umiyati (Sekolah Tinggi Ilmu Ekonomi Sutaatmadja, 2019)
The research was conducted on MSMEs located in the district of Subang. The purpose of this research is to find out the influence of accounting information system implementation and internal control on the performance of employees. The method of research is quantitative method. The sample collection technique is conducted by performing non probability sampling and Purposive sampling technique approach based on certain criteria set by the researchers using a questionnaire as a data collection tool. As for which a sample of this study were 100 respondents. Data were analyzed using multiple linear regression analysis by using computer program of SSPS (Statistical Package Social Science) V.20.0 for Windows. The questionnaire was tested for validity and reliability test. In this study using a classic assumption test including normality test, multicoloniarity test, heteroskodastisitas test. As for testing the hypothesis in this study using a test determination coefficient, F test and t test. The results of the study with multiple regression indicate that (1) the accounting information system positive and significant impact on the performance of employees, (2) internal control of positive and significant effect on the performance of employees, (3) accounting information systems and internal control, simultaneously positive and significant impact on the performance of employees. The determination coefficient analysis (R²) is 0.566 which means that the accounting information system (X1) and payment punctuality of account receivable (X2) has influence 56,6% and the remaining is 44,4% is explained by other variables which are used in this research.